FAILURE AND SURVIVAL MODEL OF A LOW-COST HOUSEHOLD WATER TREATMENT SYSTEM UTILISING LINDLEY DISTRIBUTION (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study focuses on the failure and reliability of a low-cost household water treatment system (HOWTS) using the Lindley distribution. HOWTS was designed, fabricated, and evaluated (overall efficacy and cost) in our previous studies. Data and information from these studies were utilized to evaluate and establish statistical single, Poisson, and Cox models of the efficacy and the reliability of the system. Parameters in Lindley distributions (single, 2, and 3 parameters) were determined utilising Microsoft Excel Solver (MExS) and utilized in the computation of the reliability of the system with specific attention to the treatment of turbid surface water. The accuracy of these models was measured. The study established that the overall efficacy of HOWTS was between 62.34 and 98.14 %. Reliabilities of the system were between 1.36 x 10-1 and 2.47 x 10-1, 9.53 x 10-5 and 2.26 x 10-4, and 2.43 x 10-11 and 6.11 x 10-9 for single parameter, 2 and 3 parameters of Lindley distribution, respectively. The intercept and the pore of the filter were the significant factors in the statistical regression analysis of the models for both the efficacy and reliability of the system. It was concluded that the efficacy of the system was reliable